CULTURAL PRESERVATION STRATEGY IN A MULTICULTURAL CITY: CASE STUDY OF REYOG PONOROGO IN JAKARTA: CULTURAL PRESERVATION STRATEGY IN A MULTICULTURAL CITY: CASE STUDY OF REYOG PONOROGO IN JAKARTA - Nursilah, Nursilah (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This study explores the strategies employed by the Ponorogo community in Jakarta to preserve ReyogPonorogo, an intangible cultural heritage, within a multicultural urban environment. The researchexamines the challenges and methods of cultural preservation faced by this community, highlightingthe role of community events, educational initiatives, and institutional support in maintainingcultural identity amidst globalization. Through a case study of Reyog Ponorogo in Jakarta, the paperinvestigates how traditional cultural expressions can coexist and adapt in a modern, diverse setting.It further explores the outcomes of these preservation efforts, focusing on the community’s ability toretain cultural authenticity while engaging with contemporary urban life. This research providesinsights into the broader implications of safeguarding intangible cultural heritage in rapidlyurbanizing, multicultural cities.